Imaging quantum stereodynamics through Fraunhofer scattering of NO radicals with rare-gas atoms - Onvlee, J; Gordon, S; Vogels, S; Auth, T; Karman, T; Nichols, B; van der Avoird, A; Groenenboom, G; Brouard, M; van de Meerakker, S (Springer Nature, 2016)
Stereodynamics describes how the vector properties of molecules, such as the directions in which they move and the axes about which they rotate, affect the probabilities (or cross-sections) of specific processes or transitions that occur on collision. The main aspects of stereodynamics in inelastic atom–molecule collisions can often be understood from classical considerations, in which the particles are represented by billiard-ball-like hard objects. In a quantum picture, however, the collision is described in terms of matter waves, which can also scatter into the region of the geometrical shadow of the object and reveal detailed information on the pure quantum-mechanical contribution to the stereodynamics. Here we present measurements of irregular diffraction patterns for NO radicals colliding with rare-gas atoms that can be explained by the analytical Fraunhofer model. They reveal a hitherto overlooked dependence on (or ‘propensity rule’ for) the magnetic quantum number m of the molecules, and a previously unrecognized type of quantum stereodynamics that has no classical analogue or interpretation.